Pathologic Collision of Inverted Papilloma with Esthesioneuroblastoma - Sana D Karam; Ann K Jay; Cynthia eAnyanwu; Matthew Kirk Steehler; Bruce eDavidson; Pedro eDebrito; K William eHarter (Frontiers in Oncology, 2014)
Background: Inverted papilloma (IP) of the nasal cavity is a benign tumor that 0.5-4% of all nasal tumors and have been known to rarely undergo malignant transformation to squamous carcinoma an even more rarely adenocarcinoma. Synchronous association with low grade esthesioneuroblastoma (ENB) has been reported in only one case report where a small sized lesion was treated with surgery alone. Here we report the first case of invasion of IP by high grade ENB with nodal metastasis that was treated with combined modality therapy. Case Presentation: A case of a 64 year-old African American gentleman presented to the otolaryngology with a three-month history of recurrent epistaxis. Imaging revealed a large right nasal cavity mass extending into the right sphenoid sinus but without intracranial extension. Surgical pathology revealed high grade ENB invading IP. An orbitofrontal craniotomy approach was used to achieve complete resection of the mass but with positive margins. Postoperative PET/CT showed nodal metastasis. The patient was then treated with adjuvant chemoradiation and remains without evidence of disease at 42 months post-treatment. We discuss the disease presentation, histopathologic features, and disease management with literature support. Conclusion: In this very rare disease presentation where two extremely rare malignancies collide, we show that aggressive management with trimodality therapy of surgery, adjuvant radiation with stereotactic radiosurgical boost, and adjuvant chemotherapy gives excellent results. Given the natural history of the disease, however, long follow up is needed to declare complete freedom from the disease.